2006
DOI: 10.1248/bpb.29.2077
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitors of Inducible Nitric Oxide Synthase Prevent Damage to Human Lens Epithelial Cells Induced by Interferon-Gamma and Lipopolysaccharide

Abstract: We previously found that Ca 2؉ concentrations, inducible nitric oxide synthase (iNOS) mRNA, and protein expression in lenses of the Shumiya cataract rat (SCR) increase with the development of cataracts. In this study, we investigated the change in Ca

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 31 publications
1
13
0
Order By: Relevance
“…Indeed, high levels of iNOS mRNA and iNOS protein expression have been found in cataractous lenses, and oral administration of aminoguanidine, a specific iNOS inhibitor, markedly suppressed or prevented lens opacification (54,55). Carnosine is also present in the eye lenses at a high level (56,57); therefore, our result supports the hypothesis that a possible decrease during aging, as it is known in the muscle (58), could contribute to age-related cataractogenesis.…”
Section: Discussionsupporting
confidence: 82%
“…Indeed, high levels of iNOS mRNA and iNOS protein expression have been found in cataractous lenses, and oral administration of aminoguanidine, a specific iNOS inhibitor, markedly suppressed or prevented lens opacification (54,55). Carnosine is also present in the eye lenses at a high level (56,57); therefore, our result supports the hypothesis that a possible decrease during aging, as it is known in the muscle (58), could contribute to age-related cataractogenesis.…”
Section: Discussionsupporting
confidence: 82%
“…Nitric oxide donors also lead to decreases in ATP and GSH levels in the lens in organ culture (166). Treatment of the human lens epithelial cell line, SRA 01/04, with interferon-␥ and LPS leads to iNOS expression, a decrease in ATP levels, and an increase in Ca 2ϩ -ATPase activity, effects that are attenuated by NOS inhibitors (73,104).…”
Section: Nitrogen Oxides In the Lens In Relation To Connexins And Catmentioning
confidence: 99%
“…* p<0.01 vs normal ZL rats the vitreous body was elevated in diabetic retinopathy, endotoxin-induced uveitis and traumatic cataract [31][32][33]. Furthermore, it has been shown that the apoptosis of human LECs stimulated by LPS and interferon-γ is accompanied by the induction of iNOS [34]. A nitric oxide synthase inhibitor attenuates cataract formation when exposed to high levels of glucose in vitro.…”
Section: Discussionmentioning
confidence: 99%